MAKNA ALAK TOGA DALAM TRADISI LAMARAN PADA MASYARAKAT NON MUSLIM DI DESA SIGAPOKNA KEC. SIBERUT BARAT KAB. KEPULAUAN MENTAWAI - Indah Permata Sari; Yuhelna Yuhelna; Yenita Yatim (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
One part of the culture of society is the tradition of marriage. Tradition in marriage is something that is important because it does not only concern the bride and groom, but also the relationship between the bride and groom. And this marriage tradition is also still carried out in Siberut Island Village, Mentawai Regency, one of which is the alak toga tradition. The aim of this research is to describe the meaning of alak toga (dowry) in marriages in Sigapokna Village, West Siberut District, Mentawai Islands Regency. The theory used in this study is the theory of symbolic interactionism by Herbert Blumer. The research was conducted in the village of Sigapokna, West Siberut District, Mentawai Islands Regency. This study uses a qualitative research method with a descriptive research type. Withdrawal of informants was carried out by using purposive sampling technique. The data collection method in this study began with observation, interviews, and document study. Data analysis techniques in research can be carried out in several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The results of the study show that there are several symbolic meanings for the objects carried when the alak toga tradition is carried out. These objects include: 1) Cauldron. 2) Pot, 3) Machete and 4) Mosquito Net.